"Please Let This be the Crassest Thing My Child Reads!": Exploring Community Perceptions of Challenged Children's Literature. Issue 5 (3rd July 2020) - Hartsfield, Danielle E.; Kimmel, Sue C.
Abstract: Research suggests fear of parental backlash is a primary reason why teachers preemptively censor books, yet parents' beliefs about challenged children's books are understudied. This study's purpose was to investigate adults' beliefs about challenged children's literature as expressed through reading and discussing challenged books within an adult book club at a public library. Contributions from the seven participants revealed three themes in the way they discussed challenged children's books, including making judgments about what constitutes a good book, describing engagement with the books, and the imperative of adults to make book selections on behalf of children. The findings suggest that some adults see value in reading challenged literature and their beliefs about what is appropriate for children are malleable. These findings challenge one of teachers' main rationales for engaging in preemptive censorship, and additionally, they have implications for practice as teachers consider how they utilize challenged literature in school settings.